Financial Market Theory of Development – evidence from Palestine and Israeli Stock Exchanges - Abdul Razak Abdul Hadi,; Yap, Eddy Tat Hiung; Shadi Ali Hamad,; Tahir Iqbal, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study is compelled by the motivation to find out potential equilibrium and dynamic relationships involving two neighboring stock exchanges - Palestine Stock Exchange (PEX) and Tel Aviv Stock Exchange (TASE). Based upon Financial Market Theory of Development, we attempt to explore the degree of integration between the two exchanges using Engle-Granger Cointegration procedures (1987). Data were collected on monthly basis over sample period from January 1998 till February 2012. The empirical results from bivariate Error Correction Model (ECM) reveal a statistically significant long-term relation between the two exchanges. However, the results from Granger Causality tests indicate absence of short-term relationships between them. To unveil Granger Causality in a dynamic context, we use out-of-sample testing via Impulse-Response Functions (IRF) and Variance Decompositions (VDC.) Interestingly, both tests show that performance of TASE does affect its archrival.